Absence of an Engineering-Based Approach in the Construction of Discriminatory Stereotypes Toward Women of Color: A Case Study on the Drimer Mattress Commercial - Mileydi, Flores Fernández; Junior, Llanos Flores, Marcel; Elmer, Llanos Diaz; Isabel, Castañeda Palomino, María; Enrique, Samillán Ayala, Alberto; Santos, Nauca Torres, Enrique (Journal of Cultural Analysis and Social Change, 2025)
Advertising has become a clear example of influence on the public imagination, as it shapes, arranges, and generates trends around specific contexts, topics, people, races, ideologies, and more. In 2018, the Drimer mattress commercial by Saga Falabella sparked significant controversy due to its racially stereotyped content and its impact on public perception, as well as the ethical concerns surrounding its production and dissemination. The central research question driving this study is: What are the ethical implications of the absence of an engineering-based approach in the construction of discriminatory stereotypes toward racialized women in advertising content, specifically in the case of the Drimer mattress commercial by Saga Falabella released in 2018?. The purposes of this research are, first, to analyze how the representation of stereotypes can negatively influence public perception and perpetuate discrimination in the absence of an engineering-based approach. Second, to discuss the ethical responsibility of companies to avoid harmful advertising practices and to promote inclusive and respectful representation. The methodology is qualitative, phenomenological in nature, with a socio-critical analysis; it is also emancipatory and propositional. The conclusion drawn from the ethical analysis of the Drimer mattress commercial, along with the review of academic studies on the representation of racial and discriminatory stereotypes in advertising, emphasizes the urgent need to address and correct these practices. It is essential that companies commit to the continuous training of their creative teams in matters of inclusion and diversity. Ethical responsibility in advertising is both an obligation and a strategic opportunity.